Fornix Integrity Is Differently Associated With Cognition in Healthy Aging and Non-amnestic Mild Cognitive Impairment: A Pilot Diffusion Tensor Imaging Study in Thai Older Adults - Srisaikaew, Patcharaporn; Wongpakaran, Nahathai; Anderson, Nicole D.; Chen, J. Jean; Kothan, Suchart; Varnado, Pairada; Unsrisong, Kittisak; Mahakkanukrauh, Pasuk (Frontiers in Aging Neuroscience, 2020)
Damage to the fornix leads to significant memory impairment and executive dysfunction, and is associated with dementia risk. We sought to identify if fornix integrity and fibre length are disrupted in MCI and how they associate with cognition. Data from 14 healthy older adult controls (HC) and 17 subjects with non-amnestic mild cognitive impairment (n-aMCI) were analyzed. Diffusion tensor imaging (DTI) at 1.5T MRI was performed to enable manual tracing of the fornix and calculation of DTI parameters. Higher fractional anisotropy of body and column of the fornix was associated with better executive functioning and memory, more strongly in the HC than n-aMCI group. Fornix fibre tract length (FTL) was associated with better executive function, more strongly in the n-aMCI than in the HC group, and with better memory, more strongly in the HC than n-aMCI group. These results highlight a decline in the contributions of the fornix to cognition in n-aMCI, and suggest that maintenance of fornix FTL is essential for sustaining executive functioning in people with n-aMCI.